Raman spectroscopy of graphene: probing phonons, electrons and electron-phonon interactions. - Leandro Malard Moreira (2009)
Since the identification of mono and few graphene layers in a substrate in 2004, intensive work has been devoted to characterize this new material. In particular, Raman spectroscopy played an important role in unraveling the properties of graphene systems. Moreover resonant Raman scattering (RRS) in graphene systems was shown to be an important tool to probe phonons, electrons and electronphononinteractions. In this thesis, by using different laser excitation energies, we obtain important electronic and vibrational properties of mono- and bi-layer graphene. For monolayer graphene, we determine the phonon dispersion near the Dirac point for the in-plane transverse optical (iTO) mode and the in-plane longitudinal acoustic (iLA) mode. These results are compared with recent theoretical calculations for the phonon dispersion around the K point. For bilayer graphene we obtain the Slonczewski-Weiss-McClure band parameters. These results show that bilayer graphene has a strong electron-hole asymmetry, which is larger than in graphite. In a gating experiment, we observe that the change in Fermi level of bilayer graphene gives rise to a symmetry breaking, allowing the observation of both the symmetric (S) and anti- symmetric (AS) phonon modes. The dependence of the energy and damping of these phonons modes on the Fermi level position is explained in terms of distinct couplings of the S and AS phonons with intraand inter-band electron-hole transitions. Our experimental results confirm the theoretical predictions for the electron-phonon interactions in bilayer graphene. We also study the symmetry properties of electrons and phonons in graphene systems as a function of the number of layers, by a group theory approach. We derive the selection rules for the electron-radiation and for the electron-phonon interactions at all points in the Brillouin zone. By considering these selection rules, we address the double resonance Raman scattering process. The selection rules for monolayer and bilayer graphene in the presence of an applied electric field perpendicular to the sample plane are also discussed.